2019
DOI: 10.1111/jocn.15009
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of noninvasive and invasive sialorrhoea management

Abstract: Aims and objectives To review published literature pertaining to the management of sialorrhoea while also highlighting the significance of the multidisciplinary approach. Background Sialorrhoea is a common and troublesome problem among certain neurological patients. It is distressing for patients and caregivers, and can be challenging for healthcare professionals. Various sialorrhoea management approaches have been documented. However, there is no clear consensus on best management practices. Therefore, it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…Most studies have focused on swallowing output in the context of reducing aspiration risk rather than sialorrhoea 42 . One systematic review assessed non‐invasive management of sialorrhoea across a range of etiologies including PD and concluded that studies consistently showed positive results relating to a decrease in sialorrhoea but with insufficient long term effects 43 . The likelihood of adverse events is low but there is little to suggest long lasting improvements can be made with these strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have focused on swallowing output in the context of reducing aspiration risk rather than sialorrhoea 42 . One systematic review assessed non‐invasive management of sialorrhoea across a range of etiologies including PD and concluded that studies consistently showed positive results relating to a decrease in sialorrhoea but with insufficient long term effects 43 . The likelihood of adverse events is low but there is little to suggest long lasting improvements can be made with these strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Another potentially useful antisecretory drug would be constituted by scopolamine patches, which, however, are not free from anticholinergic side effects (e.g., blurred vision and urinary retention) [ 49 , 50 ]. However, in our literature search anticholinergic drugs were reported for the treatment of neurological chronic drooling [ 51 , 52 ], or for the prevention of sialocele or the treatment of salivary fistulas following parotid surgery [ 53 , 54 ], while no mention as a possible treatment for PCF was found. For the sake of completeness, we found that successful use of combination treatments, such as scopolamine + botulinum toxin for a post-parotidectomy fistula [ 55 ], or scopolamine + NPWT for treating an entero-cutaneous fistula after esophagectomy [ 56 ], was also presented in case reports.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst anti-muscarinic drugs are routinely used first line for the management of secretions, there is a limited evidence base to determine what drug should be used and at what dose. [13] The UK National Institute for Health and Care Excellence (NICE) has recommended future research in this area. [9] The notion of determining suitability for gastrostomy on a pulmonary function threshold alone is coming into question.…”
Section: Prognosismentioning
confidence: 99%